Identity of coral reef herbivores drives variation in ecological processes over multiple spatial scales. Issue 4 (26th April 2019) - Ruttenberg, Benjamin I.; Adam, Thomas C.; Duran, Alain; Burkepile, Deron E.
Abstract: Overexploitation of key species can negatively impact ecosystem processes, so understanding the ecological roles of individual species is critical for improving ecosystem management. Here, we use coral reefs and the process of herbivory as a model to examine how species identity of consumers influence ecosystem processes to inform management of these consumers. Herbivorous fishes can facilitate the recruitment, growth, and recovery of corals by controlling the fast‐growing algae that can outcompete corals for space. However, herbivorous fish guilds are species rich with important differences among species in diet, movement, and habitat preferences. Yet, we lack a general understanding of (1) how these species‐specific differences in feeding and behavior scale up to reef‐wide rates of ecosystem processes and (2) how species identity and diversity impact these processes. To address these knowledge gaps, we used field observations to derive key species‐ and size‐specific foraging parameters for nine herbivorous parrotfish species on coral reefs in the Florida Keys, USA. We then combined these foraging parameters with fish survey data spanning multiple spatial scales to estimate the rates of three ecosystem processes: area of reef grazed, amount of macroalgae removed, and rate of bioerosion. We found that predicted rates of ecological processes varied dramatically among habitats and among reef zones within habitats, driven primarily by variation in abundance among species with different foraging behaviors. In some cases, assemblages with similar levels of total biomass had different rates of ecological processes, and in others, assemblages with different biomass had similar rates of ecological processes. Importantly, our models of herbivory using species‐specific parameters differed from those using genus‐level parameters by up to 300% in rates of ecological processes, highlighting the importance of herbivore identity in this system. Our results indicate that there may be little overlap in the roles species play, suggesting that some systems may be vulnerable to loss of ecological function with the reduction or loss of just a few species. This work provides a framework that can be applied across the region to predict how changes in management may affect the ecological impact of these important herbivores.